Persistent Increased Enteric Glial Expression of S100β is Associated With Low-grade Inflammation in Patients With Diverticular Disease. Issue 6 (July 2019) - Cossais, François; Leuschner, Sebastian; Barrenschee, Martina; Lange, Christina; Ebsen, Michael; Vogel, Ilka; Böttner, Martina; Wedel, Thilo
Abstract : Background: Diverticular disease (DD) is a common gastrointestinal inflammatory disorder associated with an enteric neuropathy. Although enteric glial cells (EGCs) are essential regulators of intestinal inflammation and motility functions, their contribution to the pathophysiology of DD remains unclear. Therefore, we analyzed the expression of specific EGC markers in patients with DD. Materials and Methods: Expression of the glial markers S100β, GFAP, Sox10, and Connexin 43 was analyzed by real-time quantitative PCR in colonic specimens of patients with DD and in that of controls. Protein expression levels of S100β, GFAP, and Connexin 43 were further analyzed using immunohistochemistry in the submucosal and myenteric plexus of patients with DD and in that of controls. Expression of the inflammatory cytokines tumor necrosis factor-α and interleukin-6 was quantified using qPCR, and infiltration of CD3+ lymphocytes was determined using immunohistochemistry. Results: Expression of S100β was increased in the submucosal and myenteric plexus of patients with DD compared with that in controls, whereas expression of other glial factors remained unchanged. This increased expression of S100β was correlated to CD3+ lymphocytic infiltrates in patients with DD, whereas no correlation was observed in controls. Conclusions: DD is associated with limited but significant alterations of the enteric glial network. The increased expression of S100β is associated with a persistent low-grade inflammation reported in patients with DD, further emphasizing the role of EGCs in intestinal inflammation. Abstract : Supplemental Digital Content is available in the text.